The Effect Foreperiod and Time Intervals between Stimuli on the Psychological Refractory Period: Evidence for Preparation - Kambiz Nouri; Seyede Nahid Shetab Booshehri; Mohammadreza Doustan (University of Tehran, 2021)
Given the importance of preparation to respond to two stimuli in different sport conditions, the aim of this study was to investigate the effect of foreperiod and time intervals between two stimuli on psychological refractory period (PRP) in athletes. This study was semi-experimental with a within-group design and fundamental-applied in terms of objectives. 50 male athlete students of Shahid Chamran University of Ahvaz (age range 22.47±1.45 years) were selected by convenience sampling method. A five-core processor ASUS notebook, Edinburgh Handedness Questionnaire, software and hardware to measure the psychological refractory period were used in this study. Participants responded to two visual (selective) stimuli that were presented with short time intervals as quickly as possible. Tests were conducted in dual tasks and single tasks in foreperiods of 1,2,4,8 s and time intervals of 100, 250, 500, 800 ms randomly. The data were analyzed using mean, standard deviation, within group analysis of variance at significance level (P<0.05). The results showed that the effects of foreperiod and the stimuli intervals were significant. The foreperiod of 1s and interval of 100 ms had the most psychological refractory period and foreperiod of 8s and interval of 800 ms had the lowest psychological refractory period. This study showed that the pattern of psychological refractory period was affected by experimental manipulation of the preparation processes when recognizing the stages of information processing. Contrary to the common belief that preparation time operates on premotor processes, in the present study preparation time operates on late motion processes and confirms the existence of processing bottlenecks in dual tasks